Răspunsuri

2014-08-10T14:50:05+03:00
 Fie a -I nr. iar b-II nr
avem ca M a=a+b/2
Iar M g=√a+b
 DEci
 Ma=26= 16+36/2 = 52/2=26
 Mg=√ 16*36 =√ 576=24
R/s : a=16 b =36
mg este egal cu radical din produsul numerelor dar mersi
2014-08-10T14:59:40+03:00
Ma=(a+b)/2=26

a+b=2*26

a+b= 52
a=52-b

√ab=24

ab= 576
a+b=52
a=52-b

b(52-b)=576

52b -b² =576

52b-b² -576 =0 |-1

b² -52b +576 =0

a=1
b = -52
c= 576

Δ = 2704 -4*576 =2704-2304= 400

x1;x2= (52 + /- √400)/2=  (52 +/- 20)/2

x1= (52+20)/2= 72/2=36

x2= (52-20)/2= 32/2= 16

b² -52 +576=0

(x-36)(x-16)=0

x-36=0  ∧  x-16=0
x=36          x=16

b=36  ∧  a=16